NON-DESTRUCTIVE MEASUREMENT OF TOTAL SOLUBLE SOLID (TSS) CONTENT OF DATES USING NEAR INFRARED (NIR) IMAGING - Manickavasagan, A.; Ganeshmoorthy, K.; Claereboudt, M. R.; Al-Yahyai, R.; Khriji, L. (Emirates Journal of Food and Agriculture, 2014)
The total soluble solid (TSS) content is one of the important quality attributes that determines the commercial value of dates. At present, TSS content in dates is measured using destructive techniques that are laborious and time consuming. In this study, the potential of a near infrared (NIR) imaging technique to determine TSS content of dates was evaluated. Date samples of three cultivars (Fardh, Khalas and Naghal) at tamar stage (n=400 fruits) and two ripening stages (tamar and khalal) of Khalas cv. (n=400 fruits) were used in this study. The area scan NIR camera which covers the full spectrum range of 900‒1,700 nm was used to capture the images of individual date fruits. Immediately following image acquisition, the TSS content (ºBrix) of each sample was measured using a digital refractometer. The TSS content of dates was in the range of 34‒63° Brix and 14‒37°Brix for tamar and khalal stages, respectively. Similarly, the percentage of NIR reflectance was 12‒38 and 39‒64 for tamar and khalal stages, respectively. A multiple linear regression (MLR) prediction model along with a dummy variable concept was established between measured TSS and NIR reflectance. NIR reflectance was inversely proportional to the TSS content of dates. The correlation coefficient (r) between TSS content and NIR reflectance was 0.62 and 0.98 for three cultivars and two ripening stages, respectively. The high correlation among ripening stages indicates the opportunities of NIR technique for potential applications in influencing ripening stages. However, further work is warranted to determine the correlation between TSS and NIR reflectance in different ripening stages of other cultivars.